Various models of Beckman pH meters - Hesketh, Dean D. (1960)
This group photograph appears to include Models G, N, N2, 72, and Pocket pH meters. Arnold Beckman invented his first pH meter in 1934 at the request of a chemist from the California citrus industry, who needed an accurate way to measure the acidity of his product. The resulting instrument kicked off rapid development not only of Beckman Instruments, Inc. but also of the electronic scientific instrument industry.
Keywords: Hydrogen-ion concentration--Measurement--Instruments; Scientific apparatus and instruments; Hydrogen-ion concentration; Beckman Instruments, Inc.